2020
DOI: 10.2196/21939
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging a Cloud-Based Critical Care Registry for COVID-19 Pandemic Surveillance and Research in Low- and Middle-Income Countries

Abstract: The COVID-19 pandemic has revealed limitations in real-time surveillance needed for responsive health care action in low- and middle-income countries (LMICs). The Pakistan Registry for Intensive CarE (PRICE) was adapted to enable International Severe Acute Respiratory and emerging Infections Consortium (ISARIC)–compliant real-time reporting of severe acute respiratory infection (SARI). The cloud-based common data model and standardized nomenclature of the registry platform ensure interoperability of data and r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The study will adhere to the FAIR (Findability, Accessibility, Interoperability, and Reusability) guiding principles of data management and sharing 40. In-built dashboards will provide accrued metadata on screening for AF, eligibility, participant recruitment, data quality and prevalence of AF and other non-communicable diseases in the study population 38 41. Weekly debriefs between the study team and data collectors will be used to discuss progress and address any challenges arising.…”
Section: Methods and Analysismentioning
confidence: 99%
“…The study will adhere to the FAIR (Findability, Accessibility, Interoperability, and Reusability) guiding principles of data management and sharing 40. In-built dashboards will provide accrued metadata on screening for AF, eligibility, participant recruitment, data quality and prevalence of AF and other non-communicable diseases in the study population 38 41. Weekly debriefs between the study team and data collectors will be used to discuss progress and address any challenges arising.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Registry structure for established registries in India, Pakistan and Nepal was already published 15 , 19 , 21 . In brief, the CCA platform has a modular structure, where a core dataset of 33 variables captured within the first 24 hours of admission to ICU and 5 variables at discharge, provides episodic information to enable evaluation of case mix, acuity, organ support and outcomes 19 , 22 .…”
Section: Methodsmentioning
confidence: 99%
“…The existing CCA registry data structure allows for site specific variation, with a common data dictionary to enable transformation of data before export 11 . Study variables such as laboratory tests are reported in the intensive care units’ routine unit of measurement.…”
Section: Approachmentioning
confidence: 99%